Making knowledge useful: 'Abd al-Samad al-Palimbani's application of al-Ghazzoli's teachings in the Malay world - Moris, Megawati (2010)
Shaykh ‘Abd al-Samad al-Palimbani, an eighteenth century scholar of Malay-Arab descent wrote a Malay-Jawi text entitled Siyar al-salikin ila ‘ibadat rabb al-‘alamin. The Siyar al-salikin is a translation-cum-commentary of the Mukhtasar ihya’ ‘ulum al-din written by Abu Hamid al-Ghazzali. It has been acknowledged that with this work, ‘Abd al-Samad successfully transmitted al- Ghazzali’s teachings to the Malays which left a great impact on their religious life and thought. Of greater significance however, and which is more our concern in this paper, is his application of al-Ghazzali’s teachings in his attempt to solve the problems of an intellectual and religious nature faced by the Malay community during his time. ‘Abd al-Samad perceived the basic problem faced by the Malays was their confusion on the orthodoxy of the Sufi tradition as intellectually adhered and religiously practiced by some of the Malay scholars and their followers in the Sufi orders (turuq). He connected this problem to two main factors: first, the lack of knowledge among the Malays on the essential teachings of tasawwuf; and second, the scholars who suffered from selfdelusion and who misled their students. In this paper, I will show how in the Chapter on the Censure of Self-Delusion (ghurur; terpedaya) in the Siyar al-salikin, ‘Abd al-Samad approached the problem and gave his solutions. Firstly, he used his authority and knowledge with the support of other scholars in the al- Ghazzalian tradition of Sufism to validate the orthodoxy of these groups. Secondly and more creatively, by using his encyclopedic scholarship he provided an extensive bibliography of over a hundred titles of works on Sufism and categorized them for each stage of study to ensure qualification to access esoteric knowledge as well as avoiding misunderstanding of doctrines. In this way, ‘Abd al-Samad made al-Ghazzali’s spiritual teachings relevant and useful to the Malays in their attempt to discern truth from falsehood when dealing with various currents of thought and beliefs prevailing at that time. It is evident that the problems faced by Malay-Muslims three hundred years ago remain relevant and important today. Hence, following Shaykh ‘Abd al-Samad’s footsteps, we can like him respond creatively and draw from our Islamic intellectual tradition to solve our present predicament.